The effects of “Treadmill training program” compared to “Endurance and strengthening exercise program” on walking and balance in the elderly - นิตุธร ชุติมา; อิฐรัตน์ กุลณัฐ; เกรียงสี่หมื่น ดมิศรา (Journal of Health Science of Thailand, 2026)
There is inceasing number of elderly people in Thailand, and more than three million of elderly people fall every year. Poor balance or weakness of leg muscles can cause risk of fall and falling can cause bbone fracture, bedridden patient, or death. Then falling problem have to be solved. The objective of this research was to find out the effect of treadmill training program compared to the effect of endurance and strengthening exercise program on walking and balance in the elderly. There were 52 elders at risk of fall were randomly divided into 2 equal groups. Group 1 (n=26) received “treadmill training program” with body weight supported, while group 2 (n=26) received “endurance and strengthening exercise program”. The elders of both groups had to perform exercise 2 times a week for 6 weeks. During the training period, the level of difficulty was gradually increased. All participants were assessed through balance by timed up and go test (TUGT), five times sit to stand test (FTSST) before and after the six-week intervention period. The data were analyzed quantitatively using Wilcoxon signed rank statistics and the Mann-Whitney U test. It was found that both groups had significantly improved in TUGT and FTSST after finished the program, with p<0.01 for all variables. Comparing the 2 groups there was no significant difference in TUGT and FTSST (p>0.01). The treadmill training program and the endurance and strengthening exercise program were able to improve muscle power, balance and stability and reduce risof falling. Both programs were suitable options for rehabilitation of walking and balance of the elderly to promote the good quality of life.